Frame and casing design of second life battery energy storage systems - Kurup, Anirudh (UiT Norges arktiske universitet, 2021)
The design of the frame and casing for two types of battery storage systems was carried out through a product development process on behalf of RePack AS. The primary design objectives were clarified using an objective tree method. The main functions of the designs were explored, and the product requirements were compiled stating the various demands and wishes pertaining to the products. Design concepts were generated for each type of product presented which resulted in two detailed concepts, with one having a prototype made at labs in UiT Narvik. The concepts presented are supported with calculations, finite element analysis using ANSYS R1 2021 academic, and material selection using ANSYS academic Granta.